(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2018)
A biolaw doctrine theorized 3 fundamental principles, the so called OUA Principles (the 3 A in Italian) in order to applicate law to the genetic field: openness, updating, attention. This article explains how the application of these principles (for extension of biolaw principles) to the Intellectual Property could help to clear up the confusion on gene patents and their incompatibility with fundamental rights. Moreover, this operation could build a clear interpretation of Intellectual Property law that might be able to encourage research.